(untitled) (Annual of the Faculty of Philosophy in Skopje, 2016)
Migration flows from the territory of Macedonia have developed and changed throughout different historical periods. After the disintegration of Yugoslavia, migration flows from Macedonia differ significantly from traditional forms of migration. The most characteristic examples are the migration of highly skilled and educated persons or brain drain, migration flows caused by the introduction and liberalization of the visa regime within the European Union and the increased mobility of the population caused mainly by the effects of globalization. Despite these migratory movements, Macedonia witnesses a reverse migration flow as well, i.e. Return migration in the country of origin. Although the number of return migrants does not exceed those of migrants from Macedonia, this phenomenon, however, has incited our research interest. This paper will analyze the benefits of returning migrants and their role in the society and it will present several examples of successful migrant returnees and their economic activities in Macedonia. The research, besides the presentation of the qualitative results from a minor study, aims to encourage further research in the area, and to open a debate on the problems of migration in Macedonia.